Investigation of the Orthopedic Problems that Affect Productivity at Establishments - Korkmaz, Murat; Kilic, Bulent; Yucel, Ali Serdar; Gurkan, Ayca; Atalay, Ahmet; Ciftci, Isa (Kamla-Raj Enterprises, 2015)
This study is an applied research that examines the impact of orthopaedic problems that the employees and personnel working at manufacturing establishments on labour productivity and performance. This applied research was carried out with the personnel working at manufacturing establishments in Istanbul, Bursa, Izmir and Ankara. 5-point Likert scale and a questionnaire were employed in the study with the aim of identifying the demographic features of the participants. This questionnaire was given to the personnel in person or sent via e-mail. Simple Random Scale was used in the study. No identity information of the participants was disclosed. The study lasted for almost 14 months. Within this period, (N=982) individuals participated in the study. At the end of the study, it was stated that work place conditions of the participants were unhealthy, unsafe, and physically uncomfortable and ergonomically insufficient. Besides, the study showed that labour productivity and performance of the personnel who experience physical, orthopaedic and traumatological problems is decreased.
Keywords: Orthopedics; Traumatology; Labour; Productivity; Performance; Physical Problems